Hubungan antara Persepsi Peranan Mamak dengan Kepatuhan pada Otoritas dalam Adat Minangkabau di Kabupaten Lima Puluh Kota Pada Generasi Z - Syahdiah, Moilinggo Rindu; Aulia, Prima (YASIN, 2024)
Along with the development of technology and modernization at this time it can influence the existence of a culture that has been inherited by ancestors. This research aims to determine the relationship between the perception of the role of mamak and obedience to authority in Minangkabau in Limapuluh Kota Regency in generation z. This research uses quantitative methods with a correlational approach. Meanwhile, the subjects in this study were 123 generation z in Limapuluh Kota Regency, where the subjects were native residents of Minang ethnic descent who lived in Limapuluh Kota Regency. This research uses a cluster sampling technique. The data collection method in this research uses a scale of obedience to authority with a reliability of 0.894 while a perception scale with a reliability value of 0.867. This research uses product moment correlation data analysis with the help of the Statistical Package for Sciences (SPSS) 26.0 for Windows program to obtain hypothesis results with a value of r = 0.706 with a significance value of p = 0.00 (p < 0.05). This shows that there is a positive relationship between perception and obedience to authority in Limapuluh Kota Regency in generation z, the higher the obedience to authority in generation z, the higher (better) the resulting perception. It can be concluded that the results of this study show that obedience to authority and perceptions in Limapuluh Kota Regency in the z generation tend to be high in the medium category.